Peningkatan Pendapatan Warga Desa Tlagayasa Melalui Pemberdayaan Ibu-Ibu dan Karang Taruna - Siti Rahmah Nurshiami; Triyani Triyani; Supriyanto Supriyanto; Jajang Jajang; Agung Prabowo (Pasca Sarjana | Universitas Jenderal Soedirman, 2021)
Tlagayasa Village is located in Bobotsari District, Purbalingga Regency. Most of the Tlagayasa villagers work as farmers. The absence of a guarantee of harvest results will pose a risk of crop failure for farmers so that it will result in reduced income for farmers. Mothers Fostering Family Welfare (PKK) and teenage children in Tlagayasa village need to be empowered so that they can help increase family income. PKK members can empowered in producing floor cleaners, while teenage children are empowered in marketing. The activity begins with socialization, training making of floor cleaners, monitoring production and marketing of floor cleaners through social media. The result of this activity is the establishment of a floor cleaning home-industry